Critical success factors of strategic alliance in the shipping industry - Lu, Hui Ting (2024)
Attributing to multiple environmental, organisational and cultural factors, shipping alliances (SAs) are complex and challenging to manage. This study aims to identify and categorise the critical success factors (CSFs) in SAs using a theory-driven approach. Moreover, it looks to examine their effects on two vital outcomes in SAs, including opportunistic behaviour (OB) and constructive coordination (CC). The CSFs were categorised into phases: 1) alliance rationale and conditions; 2) partner search and selection; 3) partnership design; 4) partnership implementation; 5) partnership outcome evaluation. A survey questionnaire was then drafted and administered to 180 executives from all shipping lines involved in major SAs (i.e., 2M, Ocean Alliance and The Alliance). Thereafter, the data were analysed using exploratory factor analysis and structural equation modelling. The findings validated the categorisation of the 20 CSFs. Furthermore, it was found that the CSFs have direct and indirect effects on CC via OB.